Application of evidence based practice: Interdialytic weight gain (IDWG) management intervention in hemodialysis patients at Arifin Hospital, Riau - Erni Forwaty; Nia Khusniyati; Usraleli Usraleli (Universitas Muhammadiyah Magelang, 2022)
The physical problem that is often experienced by hemodialysis (HD) patients and is difficult to overcome is the problem of excess fluid. This can be seen from the patient's weight gain between dialysis times or called interdialytic weight gain (IDWG). A high IDWG is associated with a higher risk of cardiovascular causes of death and increased morbidity. The application of evidence based practice in the form of IDWG management interventions has been proven to be able to overcome excessive weight gain between the two HD or IDWG times. The purpose of this community service is to increase the knowledge and skills of HD patients regarding evidence based practice in the form of IDWG management interventions. The method of implementing community service activities is in the form of training packaged with HD patients on IDWG management with lectures, questions and answers, and demonstrations. The resulting impact is an increase in the knowledge and skills of HD patients regarding IDWG management with a standard percentage of IDWG weight gain of 22% and IDWG weight loss >3.5% of 14% after implementing IDWG management. In addition, the patient has been able to apply techniques to overcome thirst and xerosemia. Nurses and the patient's family must take part in providing support for patient compliance in implementing IDWG management so that patients can avoid complications from excess fluid problems which can ultimately improve the patient's quality of life.